Pengaruh Budaya Populer Korea terhadap Perilaku Modeling Siswa Madrasah Aliyah Negeri - Aufa, Ari Abi; Mufid, Miftahul; Wahdani, Firda Rizka Rachma (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aimed to examine the existence of Korean popular culture on the modeling behavior of class XI students at MAN 1 Bojonegoro. The research approach used is quantitative with the correlation method. The sampling technique used is purposive sampling. Data were collected using a questionnaire distributed to 100 students of class XI MAN Bojonegoro. The data that has been obtained is then processed using the Pearson Product Moment formula through SPSS Version 25 for Windows. Based on the results of simple linear regression analysis with the t-test, it can be seen that the t-value of the popular culture variable is 21.849, while the t-table value is 2.01174. The calculated t value is more significant than the t table, so it can be concluded that the popular culture variable (X) significantly affects the modeling behavior variable (Y).